1987
DOI: 10.1093/ajcn/46.2.346
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency and interleukin 1 production by rat leukocytes

Abstract: The production of the immunotransmitter, interleukin 1 (IL-1), by peritoneal exudate cells (PEC) was examined in iron-deficient and control rats. Three groups of weanling male Sprague-Dawley rats were fed a purified diet containing 6, 12, or 35 ppm iron for 6 wk to produce severe iron deficiency, moderate iron deficiency, or adequate iron status. Crude IL-1 samples were prepared from acute PEC and assayed for activity. IL-1 preparations from severely and moderately iron-deficient rats enhanced mouse thymocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 29 publications
0
12
1
2
Order By: Relevance
“…There is some preliminary evidence in mice to suggest that iron deficiency may impair macrophage function (39). Macrophages from iron deficient mice have been shown to have impaired phagocytic activity and reduced interleukin I production (40).…”
Section: Non-specific Immunitymentioning
confidence: 99%
“…There is some preliminary evidence in mice to suggest that iron deficiency may impair macrophage function (39). Macrophages from iron deficient mice have been shown to have impaired phagocytic activity and reduced interleukin I production (40).…”
Section: Non-specific Immunitymentioning
confidence: 99%
“…At the systemic level, studies in experimental animals and humans have shown that administration of TNF-α suppresses serum iron concentration [25-27]. Not only does inflammation affect iron metabolism, but iron status itself may modulate the production of inflammatory cytokines [28-30]. Iron deficiency anemia in infants was reported to increase lipopolysaccharide-induced production of tumor necrosis factor-α by peripheral blood mononuclear cells [29].…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of cellular iron homeostasis is not only a general prerequisite for the growth and proliferation of all cells but is also of central importance for the regulation of the immune function. Iron status has been reported to modulate cytokine secretion [3, 4]. In general, iron has been reported to direct the immune response towards a Th2 response pattern [5, 6] that is believed to be unfavourable for the killing of many intracellular pathogens.…”
Section: Introductionmentioning
confidence: 99%